The reality of Sustainable Leadership practice: An exploratory study on King Saud University During the period January to February of 2023 - Alamri, Majd Talal; Alaiban, Khalid Mohammed (Journal of Economic, Administrative and Legal Sciences, 2023)
The research aimed to identify (the reality of foundational practices, the reality of high-level practices, and the reality of key incentive practices) for sustainable leadership at King Saud University. The researcher used the descriptive survey method using the questionnaire. The research community consisted of all university employees, as the research sample amounted to (397) male and female employees. The most prominent results of the research: The members of the research sample agree to a moderate degree on the foundational practices of sustainable leadership at the university with an arithmetic average of (3.29 out of 5). The friendly relationship dimension between employees came in first place, followed by ethical behavior, then performance appreciation with a moderate degree, followed by the retention dimension. Long term staff Finally a dimension of continually developing personnel. It was also found that the respondents agreed to a moderate degree on the reality of high-level practices of sustainable leadership at the university, with an arithmetic average of (3.08 out of 5). The self-management dimension came in first place with a moderate degree, followed by decision-making, then the culture of empowerment, then the dimension of preserving and sharing knowledge. The results showed that the respondents agreed to a moderate degree on the reality of the main incentive practices for sustainable leadership at the university, with an arithmetic average of (3.10 out of 5). The quality dimension came in first place, followed by decision-making, employee participation, and the strategic innovation dimension. The researcher recommends the following: holding courses and workshops for university employees introducing sustainable leadership and its benefits and paying attention to spreading the culture of sustainable leadership by spreading innovation and sustainable excellence in university education.